The Study of Formaldehyde and Borax Content on Salted Fish from Several Markets in Tembilahan Indragiri Hilir, Riau - Putri Wening Ratrinia; Sumartini Sumartini; Lisa Bonita (JURNAL PERIKANAN DAN KELAUTAN, 2020)
Fisheries and marine sector is one of the potential sectors in Indragiri Hilir district, Riau. Local fishermen make efforts to preserve the catch by salting it. Although salt can extend product shelf life, there are still many salted fish producers that add formaldehyde and borax to reduce production costs. The addition of formaldehyde and borax is carried out with the aim of extending product shelf life so that producers do not lose. The aim of this study was to determine the presence of formalin and borax content in salted fish products in several markets in Tembilahan. The sampling method in this study was simple random sampling by taking three different samples of salted fish, namely salted belukang, salted kembung, and salted gulama in three different markets in Tembilahan. Samples were tested for formalin and borax using test kit. The results of the qualitative formalin content test showed that from 9 samples of salted fish from several Tembilahan markets, there were 5 positives samples containing formaldehyde. The five samples were salted salted fish belukang, salted fish kembung, salted fish gulama from central market, and salted fish gulama and salted fish kembung from Parit 11 market. In the other hand, the salted fish samples were also tested qualitatively for borax content test. The qualitative test results of borax on 9 samples from several markets in Tembilahan showed no color change on the turmeric paper after immersion in the sample solution. This indicates that all salted fish samples is negative for borax content.